Place of retinoprotective therapy in modern ophthalmologic practice - E.A. Egorov; D.A. Dorofeev (РМЖ "Клиническая офтальмология")
Egorov E.A.1, Dorofeev D.A.2 1 Pirogov Russian National Research Medical University, Moscow 2 Regional Clinical Hospital No.3, Chelyabinsk Aim: to identify the significant predictors of retinoprotective therapy. Materials and Methods: the subject of study were 87 questionnaires of ophthalmologists from 18 cities. Online survey was conducted between 01/09/2017 and 10/01/2017, a questionnaire was created on the Google-forms platform https://docs.google.com/forms/d/117AHXHnbr2i_BT5WBV6_uMFBDaPO2bzR8zlBcYhEQpI/edit. It included 8 questions: city of residence; place of work: hospital/city clinic; working experience; frequency of retinoprotective therapy prescription; reasons for retinoprotective therapy prescription: on patient’s own request / no other ways to help / patient either cannot be observed without retinoprotective therapy or the further observation is inappropriate; frequency of retinoprotective therapy prescribing for various nosologies; desired route of administration; what medications do you use most commonly? For the analysis of the most significant predictors of prescribing retinoprotective therapy for glaucoma, a model of binomial logistic regression was constructed which included all the questions of the questionnaire, then the variance analysis was used to identify the significant predictors. Results: the desired route of administration is parenteral (86% of the questionnaires). The most common medication for retinoprotective therapy is Retinalaminum (Geropharm, Russia) (22% of the questionnaires). Only 8 (9%) of respondents did not mention the use of this medication, other doctors use Retinalaminum in combination with antioxidants, glutamate antagonists, Ca2+ channel blockers, B group vitamins, lutein-containing drugs, Cortexin (Geropharm, Russia). The most common combination was the combination of Retinalaminum and Emoxipine (42%). Neither the city of residence nor the place of work, nor the frequency of prescribing retinoprotective therapy, as well as the drugs themselves, the ways of their administration, and the diseases in which they were used, were not significant predictors. Significant in prescribing retinoprotective therapy are working experience and the reasons for the prescribing retinoprotective therapy. Conclusion: the probability of appointing retinoprotective therapy increases with an increase of working experience, and if the working experience is more than 5 years the probability of prescribing retinoprotective therapy for glaucoma is 81%, which is probably due to the fact that the acquisition of clinical experience leads to realizing that without retinoprotective therapy the patient either cannot be observed or further observation will be inappropriate. Key words: glaucoma, retinoprotective therapy, Retinalamin, intraocular pressure level, questionnaire. For citation: Egorov E.A., Dorofeev D.A. Place of retinoprotective therapy in modern ophthalmologic practice //  RMJ “Clinical ophthalmology”. 2018;1:31–36.